Komparasi Hasil Belajar Mahasiswa FBS UNP Padang Berdasarkan Jalur Masuk Perguruan Tinggi - Yusron Wikarya (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2011)
This study aims at (1) describing the learning achievement of students of FBS UNP Padang based on the entrance selection modes that they have followed, (2) examining the differences of the learning achievement of the students of FBS UNP Padang based on the entrance selection modes. This research used the causal comparative ex-post facto design. The data were analyzed with the ANOVA technique. The result of data analysis shows that there is a significant difference in the learning achievement of students of FBS UNP Padang based selection paths taken. The statistical result of Tukey's test shows that the average learning achievement of students from SPMB/SNMPTN program is significantly different from the average learning achievement of students from the Non-Regular program and track record achievement program. The average learning achievement of students from PMDK program is significantly different from the average learning achievement of students from the Non-Regular program. Keywords: learning achievement, entrance selection mode